Determining The Attitudes of Nurses Towards Evidence-Based Practices - Esra Şen; Seher Yurt (Dokuz Eylul University, 2021)
Background: Evidence-based practice is the transformation of rapidly increasing research in nursing science and the results of these research into practice in clinics.Evidence-based practices have become a new alternative to nurses' search for authority to gain autonomy. Aim: This study was aimed to determine the attitudes of nurses towards evidence-based nursing practices. Method:The sample of the study, which was planned as descriptive, consisted of 92 volunteers working at foundationuniversity hospital. The research was carried out between February-April 2019. Data were collected with 'Sociodemographic Information Form' and 'Evidence Based Nursing Attitude Scale'. Frequency, Kruskall Wallis test and Z test were used in the analysis of the data. Result: 21.7% of nurses were undergraduate, 82.6% were working under 10 years, 91.3% did not follow scientific publications, 88% were not members of professional associations. It was determined that 53.3% did not take evidence-based practice courses in education, 88% did not participate in scientific research and 62% did not receive in-service training for evidence-based practice in their institution. The total average scores of nurses' attitudes towards' Evidence Based Nursing' were found 51.33 ± 5.18. It was determined that there was a significant difference between nurses' education levels, duration of employment, in-service training, participation in scientific research, and taking an evidence-based practice courses (p ˂ .05). Conclusion: Nurses' attitudes towards evidence-based nursing were found to be moderate. It was concluded that the nurses believed in the usefulness of evidence-based practices, but evidence-based beliefs did not cause behavioral changes in practice. Considering the results of the research; Including evidence-based practices in in-service training programs for nurses, establishing evidence-based practice committees in hospitals, training mentor nurses, and employing more undergraduate and graduate nurses in hospitals may be suggested.